Inactivation Effect of Thymoquinone on Alicyclobacillus acidoterrestris Vegetative Cells, Spores, and Biofilms - Fan, Qiuxia; Liu, Cheng; Gao, Zhenpeng; Hu, Zhongqiu; Wang, Zhouli; Xiao, Jianbo; Yuan, Yahong; Yue, Tianli (Frontiers in Microbiology, 2021)
Alicyclobacillus acidoterrestris (A. acidoterrestris), a spore-forming bacterium, has become a main challenge and concern for the juices and acid beverage industry across the world due to its thermo-acidophilic characteristic. Thymoquinone (TQ) is one of the active components derived from Nigella sativa seeds. The objective of this study was to investigate antibacterial activity and associated molecular mechanism of TQ against A. acidoterrestris vegetative cells, and to evaluate effects of TQ on A. acidoterrestris spores and biofilms formed on polystyrene and stainless steel surfaces. Minimum inhibitory concentrations of TQ against five tested A. acidoterrestris strains ranged from 32 to 64 μg/mL. TQ could destroy bacterial cell morphology and membrane integrity in a concentration-dependent manner. Field-emission scanning electron microscopy observation showed that TQ caused abnormal morphology of spores and thus exerted a killing effect on spores. Moreover, TQ was effective in inactivating and removing A. acidoterrestris mature biofilms. These findings indicated that TQ is promising as a new alternative to control A. acidoterrestris and thereby reduce associated contamination and deterioration in the juice and acid beverage industry.